A Framework to Predict Time and Cost Risks based on Project Factors - Mohamad Hadi Jalili; Martin Skitmore (Salehan Institute of Higher Education, 2018)
The occurrence and severity of risks are directly associated with the project factors, and in the case of determining a logical and significant correlation between project factors and risks, the final conditions of the project based on the initial and definite project factors can be predicted. In this research, a final list of 112 risks was prepared using the views of experts. Then, the risks’ weight was determined based on their impact on time and cost and according to the repetition of each risk in the earlier studies, as well as the use of 630industry experts using online web-based forms. Afterwards, 21 project factors that could affect the probability of occurrence and severity of risks related to time and cost were identified, and these factors were prioritized for each risk using the views of 25 experts. Then, applying the Pareto Principle, 14 project factors were identified. In all 4cases, including calculating the weight of risks in the technical literature as well as the experts’ views by time and cost, 14 selected factors were the same, but the weight and effects were different. The results indicate that considering these factors, the risks of time and cost increase from the initial estimate can be accurately predicted.